Exploring the synergistic effect of short jute fiber and nanoclay on the mechanical, dynamic mechanical and thermal properties of natural rubber composites. (May 2018) - Roy, Kumarjyoti; Chandra Debnath, Subhas; Das, Amit; Heinrich, Gert; Potiyaraj, Pranut
Abstract: Natural rubber (NR) composites were reinforced by suitable hybrid fillers system containing short jute fiber and stearic acid modified nano clay. The synergistic effect of short jute fiber and stearic acid modified nanoclay in NR composites was systematically evaluated in the light of cure, mechanical, morphological, dynamic mechanical and thermal properties. Synergistic interaction between short jute fiber and modified nanoclay increased the value of cure rate index (CRI) and tensile strength of NR composites successfully. Scanning electron microscopy (SEM) analysis indicated a continuous and smooth surface for the NR composites containing hybrid fillers system. Dynamic mechanical analysis (DMA) confirmed excellent improvement in the rubber/filler interaction for NR/nanoclay/jute fiber hybrid composites as compared to NR composites with single filler system. Fourier transform infrared (FTIR) study was utilized to explain the transformation of hydrophilic jute fiber surface to more hydrophobic nature in presence of stearic acid modified nanoclay. Highlights: Synergistic effect of short jute fiber and stearic acid modified nanoclay in NR composites was reported for the first time. Improvement in tensile and dynamic mechanical properties of NR/nanoclay/jute fiber hybrid composite in a synergistic way. Scanning electron microscopy showed very continuous and smooth surface for NR/nanoclay/jute fiber hybrid composite. NR-nanoclay-jute hybrid system will provide a pioneering way on the development of green elastomer technology.